2009
DOI: 10.1063/1.3254328
|View full text |Cite
|
Sign up to set email alerts
|

Charge-transfer induced surface conductivity for a copper based inorganic-organic hybrid

Abstract: Inorganic-organic hybrids are receiving increasing attention as they offer the opportunity to combine the robust properties of inorganic materials with the versatility of organic compounds. We have studied the electric properties of an inorganic-organic hybrid with the chemical formula: CuCl4(C6H5CH2CH2NH3)2. This material is a ferromagnetic insulator that can easily be processed from solution. We show that the surface conductivity of the hybrid can be increased by five orders of magnitude by covering the surf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
20
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 29 publications
(22 citation statements)
references
References 16 publications
2
20
0
Order By: Relevance
“…58 The inorganic CuCl 6 octahedra share corners to form two-dimensional sheets separated by a bilayer of organic molecules, here phenylethylammonium (PEA). 5,59 At 100 K, x-ray-diffraction data suggested that the nonpolar P bca space group (D 15 2h ) is adopted. However, pyroelectric current measurements have shown that PEACuCl is polar below 340 K, hence, the actual space group must be polar.…”
Section: Methodsmentioning
confidence: 99%
“…58 The inorganic CuCl 6 octahedra share corners to form two-dimensional sheets separated by a bilayer of organic molecules, here phenylethylammonium (PEA). 5,59 At 100 K, x-ray-diffraction data suggested that the nonpolar P bca space group (D 15 2h ) is adopted. However, pyroelectric current measurements have shown that PEACuCl is polar below 340 K, hence, the actual space group must be polar.…”
Section: Methodsmentioning
confidence: 99%
“…Hybrid organic-inorganic perovskite materials are few of the most extensively studied crystalline hybrid compounds, by virtue of their multifunctional behaviour and potential applications [1][2][3][4][5][6][7] . They consist of a wide range of inorganic anion chains (an extended network of corner-sharing metal oxide or halide complexes), alternating with large variety of organic cations as building blocks.…”
Section: Introductionmentioning
confidence: 99%
“…Our data are analyzed assuming T 1r shows a minimum when u C s C ¼ 1 and the BPP relation between T 1r and u 1 is applicable. As the T 1r curves are found to exhibit minima, it was possible to determine the coefficient, 0.05(m o /4p) 2…”
Section: Resultsmentioning
confidence: 99%
“…Hybrid organic-inorganic compounds have been known since 1976 but recently they have been revisited due to their potential use as substitute materials for perovskites. [1][2][3][4][5][6] Metal complexes with the formula (CH 3 NH 3 ) 2 MCl 4 (M ¼ Mn, Fe, Cu, Zn, Cd) can be classied into two groups from a crystal structure point of view. [7][8][9][10][11][12][13][14] One group (CH 3 NH 3 ) 2 MCl 4 (M ¼ Mn, Fe, Cd) has a perovskite-type layer structure consisting of cationic layers and layers of corner-sharing chlorine octahedra with a divalent metal ion at the center.…”
Section: Introductionmentioning
confidence: 99%